1987
DOI: 10.1111/j.1600-0714.1987.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural findings in oral Kaposi's sarcoma (AIDS)

Abstract: Ten biopsies of oral Kaposi's sarcoma were examined histologically and ultrastructurally. Histologically, early and late tumor stages could be differentiated. On the Ultrastructural level, endothelial‐like and spindle‐shaped tumor cells were revealed. Tumor cells associated with vessel‐like spaces showed partly interrupted basal membranes, Weibel‐Palade bodies, desmosomes and tight‐junctions, while spindle‐shaped cells lacked these Ultrastructural features of endothelial cells. Within the cytoplasm of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…studies in these cases revealed protrusion of endothelial ceUs, vascu!ar slit-like channels, sparseness of intercellular junctions, and extravasated erythrocytes (10,11). All of these phenomena, common and essential changes of ear!y KS stage (5,6,15), were a!so found in our study of uninvo!ved ora! mucosa.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…studies in these cases revealed protrusion of endothelial ceUs, vascu!ar slit-like channels, sparseness of intercellular junctions, and extravasated erythrocytes (10,11). All of these phenomena, common and essential changes of ear!y KS stage (5,6,15), were a!so found in our study of uninvo!ved ora! mucosa.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, hemosiderin, eosinophilic bodies and extravasated erythrocytes as well as plasma cells and lymphocytes were frequently observed in KS lesions (5,6,14), the proportion of each component varying with the clinical stage of the lesion. While the histological appearance of late-stage KS lesions, clinically presenting as nodules, is dominated by spindle cells with interspersed bloodfilled clefts, early KS lesions, clinically appearing as macules, are composed predominantly of endothelium-lined, vessel-hke structures (6,15). The appearance of cuboidal endothelial cells with enlarged nuclei and partially incomplete formation of the basal membranes has been considered to be the earliest ultrastructural hint for neoplastic growth (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular junctions between neoplastic endothelial cells are frequently defective allowing the extravasation of large numbers of erythrocytes from vessel lumens into the surrounding tissue. [50][51][52][53] These renegade cells become more numerous as the disease progresses and abnormal networks of slitlike vascular spaces expand. Erythrophagocytosis by KS cells is also a common feature.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential for increased exposure of KS cells to free heme and heme-containing proteins in KS tissue, [50][51][52][53][54] we investigated the possibility that HO-1 up-regulation might affect the response of KSHV-infected cells to heme. Overexpression of HO-1 A indicates apoptosis; TNFR1, tumor necrosis factor receptor 1; absent, protein present in mock-infected cells but not in KSHV-infected cells (fold change cannot be called); CA, cell adhesion; CD, cell division; FK506, tacrolimus; GAP, GTPase-activating protein; T-LAK, lymphokine-activated killer cells with T-cell phenotype; MAPKK, mitogen-activated protein kinase kinase; CS, cell shape; DR, DNA repair; M, metabolism; GTP, guanosine 5Ј-triphosphate; O, other; IFN, interferon; PS, protein sorting; T, transcription; TGFB, transforming growth factor beta; TG, tumorigenesis; and U, unknown.…”
Section: Ho-1 Up-regulation Increases Proliferation Of Kshv-infected mentioning
confidence: 99%